2009
DOI: 10.1007/s00224-009-9196-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Wardrop Equilibria

Abstract: We study the sensitivity of equilibria in the well-known game theoretic traffic model due to Wardrop. We mostly consider single-commodity networks. Suppose, given a unit demand flow at Wardrop equilibrium, one increases the demand by ε or removes an edge carrying only an ε-fraction of flow. We study how the equilibrium responds to such an ε-change. Our first surprising finding is that, even for linear latency functions, for every ε > 0, there are networks in which an ε-change causes every agent to change its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In a different direction, Patriksson [28] characterized the existence of directional derivatives for the equilibrium and [20] proved that equilibrium costs are always directionally differentiable, whereas equilibrium edge loads not always are. Takalloo and Kwon [14] showed that there exist single OD network games where an ε-increase in the traffic demand produces a global migration of traffic from one set of equilibrium paths to a disjoint set of paths, but, nevertheless, the load on each edge changes at most by ε. Moreover, if the cost functions are polynomials of degree at most d, then the equilibrium costs increase at most of a multiplicative factor (1 + ε) d .…”
Section: Related Workmentioning
confidence: 99%
“…In a different direction, Patriksson [28] characterized the existence of directional derivatives for the equilibrium and [20] proved that equilibrium costs are always directionally differentiable, whereas equilibrium edge loads not always are. Takalloo and Kwon [14] showed that there exist single OD network games where an ε-increase in the traffic demand produces a global migration of traffic from one set of equilibrium paths to a disjoint set of paths, but, nevertheless, the load on each edge changes at most by ε. Moreover, if the cost functions are polynomials of degree at most d, then the equilibrium costs increase at most of a multiplicative factor (1 + ε) d .…”
Section: Related Workmentioning
confidence: 99%
“…[22] and [14] perform sensitivity analysis of Wardrop equilibrium to some parameters of the model. Closer to the scope of our paper, Englert et al [9] examine how the equilibrium of a congestion game changes when either the total mass of players is increased by ε or an edge that carries an ε fraction of the mass is removed. For polynomial cost functions they bound the increase of the equilibrium cost when a mass ε of players is added to the system.…”
Section: Related Literaturementioning
confidence: 99%
“…For example, for traffic networks with separable, polynomial link costs, Correa et al (2008) showed that tighter upper bounds than those presented by Roughgarden (2003) can be derived provided the free-flow travel cost on each network link is at least a non-zero, fixed proportion of its travel cost under a UE assignment of travel demand. Englert et al (2010) also showed that the maximum increase in the Price of Anarchy, due to an increase in demand, can be bounded for traffic networks with separable, polynomial link costs and a single origin-destination (OD) pair.…”
Section: Introductionmentioning
confidence: 99%